AUTHENTIC MATERIALS FOR TEACHING READING - Astried Damayanti (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
The research was aimed to enhance the students’ reading comprehension skill by using authentic materials. Action research was conducted with two cycles. The research subjects were the fourth semester students of English Language Education Department of STKIP PGRI Trenggalek who took Extensive Reading. The research was done in two cycles with some changes of activity. The result of the research showed there was improvement of the students’ mean score. From making paraphrasing, the students’ mean score of the first cycle was 65.05 and the second cycle was 75.87. The students’ skill of reading comprehension increased by: (1) enhancing the students’ interest to read by using authentic materials, (2) improving the students’ motivation in reading activity, (3) helping the students paraphrase as one of reading evaluation. It shows that authentic materials can be used to help students improve their reading skill